A method for improving the bone integration and antibacterial ability of titanium alloy dental implants

Through thermoelectrochemical oxidation treatment, a porous coating with high phosphorus content is formed, and the problem of insufficient bone integration ability and antibacterial performance of traditional titanium alloy dental implants is solved, achieving higher biological activity and antibacterial effects.

CN118634049BActive Publication Date: 2025-03-07ZHEJIANG TAIKOUJIA BIOTECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410893688.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-03-07
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

Traditional titanium alloy dental implants have low bone integration capabilities after implantation in humans and insufficient antibacterial performance. The existing microarc oxidation process is complex and the coating quality is poor.

Method used

The thermoelectrochemical oxidation treatment method is used to treat the titanium alloy dental implant by placing an electrolyte containing phosphate, hydroxide and EDTA ions to form a porous coating, and the phosphorus content and antibacterial effect are improved by adjusting the reaction electrical parameters and zeta potential.

Benefits of technology

Improves the bone integration capability and antibacterial properties of titanium alloy dental implants, ensuring coating quality and reducing harmful metal release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118634049B_ABST
    Figure CN118634049B_ABST
Patent Text Reader

Abstract

The present application relates to a method for improving the bone integration and antibacterial ability of titanium alloy dental implants, and the specific steps are as follows: Step 1: prepare an electrolyte, the electrolyte includes: phosphate ions, hydroxide ions and EDTA ions, wherein the phosphate concentration is 5-20 mol / L, the hydroxide ion concentration is 5-10 mol / L, and the EDTA ion concentration is 1-3 mol / L; Step 2: immerse the titanium alloy dental implant substrate in the electrolyte prepared in step 1 for thermoelectrochemical oxidation treatment until a crater-shaped porous coating containing phosphorus is formed, and the conditions of the thermoelectrochemical oxidation treatment are: the positive current of the pulse power supply is 8-14A / dm2, the negative current is 6-16A / dm2, the duty cycle is 70%-100%, and the reaction time is 10-20 minutes. The titanium alloy dental implant is subjected to thermoelectrochemical oxidation treatment to form a porous coating. While ensuring the quality of the coating, the phosphorus content is further increased to improve the bone integration ability, and the antibacterial effect is achieved by changing the zeta potential to a higher positive potential, which is an effective measure to inhibit the release of harmful metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical machinery, and in particular to a surface treatment method for improving the bone integration ability and antibacterial ability of a titanium alloy dental implant. Background Art

[0002] Titanium and its alloys have excellent comprehensive mechanical properties and good biocompatibility, and are the preferred materials for medical implants. However, traditional medical titanium implants have many shortcomings, such as long healing time after implantation in the human body and low bone integration rate. In order to obtain better bone integration performance, micro-arc oxidation technology is often used to modify the implant to increase the surface roughness of the material and improve the combination between the implant and the new bone tissue, such as the methods for obtaining porous and rough surfaces disclosed in Swedish Patent Application No. 99019474-7, Swedish Patent Application No. 0001202-1 and WO2005055860.

[0003] Based on the ordinary micro-arc oxidation process, further research attempts to increase the phosphorus content in the coating to enhance bone integration ability, such as Qiao LP (LPQiao et al,, Surface & Coatings Technology 285 (2016) 187–196), Patent Publication No.: CN110180020B, etc. Use calcium acetate-EDTA disodium solution to treat at a current density of 80mA / cm2 for 2 to 6 minutes, and the maximum phosphorus content of the obtained coating is 8.19%at, for example. However, the coating with the highest phosphorus content is not the process with the longest processing time, but appears in the shortest process time of 2 minutes, and the phosphorus content has no positive proportional relationship with the processing time.

[0004] Some studies have attempted to improve the antibacterial properties by introducing silver elements into the coating. For example, patent publication number: CN107648674B, adding 0.05 mol / L of silver oxide nanoparticles to the electrolyte can form small nano silver oxide particles on the micro-arc oxidation layer, and the antibacterial efficiency against typical S. aureus bacteria exceeds 99%, for example, Reproduced with permission from Ceram. Int, 2019, 45, 22357–22367, Elsevier Ltd.

[0005] However, the micro-arc oxidation process used by the above-mentioned research institute is complex and usually uses more than 5 electrolyte solute components, which will destroy the quality of the coating (such as the coating adhesion. The coating adhesion containing phosphorus usually does not exceed 8MPa, and the atomic percentage of phosphorus does not exceed 9%). In addition, while the silver element enhances the antibacterial effect of the coating, it also has strong cytotoxicity.

[0006] Therefore, the purpose of this application is to enhance the biological activity of titanium alloy dental implants by performing thermoelectrochemical oxidation treatment on titanium alloy dental implants to form a porous coating, while ensuring the quality of the coating, further increasing the phosphorus content to enhance bone integration ability, and achieving an antibacterial effect by changing the zeta potential to a higher positive potential, which is an effective measure to inhibit the release of harmful metals. Summary of the invention

[0007] The present application relates to a method for improving the bone integration and antibacterial ability of titanium alloy dental implants, and the specific steps are as follows:

[0008] Step 1: preparing an electrolyte, the electrolyte comprising: phosphate ions, hydroxide ions and EDTA ions, wherein the phosphate concentration is 5 to 20 mol / L, the hydroxide ion concentration is 5 to 10 mol / L, and the EDTA ion concentration is 1 to 3 mol / L;

[0009] Step 2: Immerse the titanium alloy dental implant substrate in the electrolyte prepared in step 1 for thermo-electrochemical oxidation treatment until a crater-shaped porous coating containing phosphorus is formed. The conditions of the thermo-electrochemical oxidation treatment are: the positive current of the pulse power supply is 8 to 14 A / dm2, the negative current is 6 to 16 A / dm2, the duty cycle is 70% to 100%, and the reaction time is 10 to 20 minutes.

[0010] Furthermore, the electrolyte also includes sodium ions or potassium ions. Since phosphate ions, hydroxide ions and EDTA ions are anions, sodium ions or potassium ions are used for neutralization.

[0011] Furthermore, the thickness of the crater-shaped porous coating containing phosphorus is controlled to be 10 to 15 ± 1 micrometers. If the thickness of the crater-shaped porous coating containing phosphorus is higher or lower, the coating bonding strength between the crater-shaped porous coating containing phosphorus and the titanium alloy substrate will be reduced.

[0012] Furthermore, the components of the crater-shaped porous coating containing phosphorus after the treatment in step 2 are phosphorus, oxygen and titanium.

[0013] Furthermore, the phosphorus content of the crater-shaped porous coating containing phosphorus after the treatment in step 2 is 11.06% by atomic percentage.

[0014] Furthermore, the coating bonding strength between the crater-shaped porous coating containing phosphorus element and the titanium alloy substrate after the treatment in step 2 reaches 20 MPa.

[0015] Furthermore, the zeta potential of the surface of the crater-shaped porous coating containing phosphorus element after the treatment in step 2 is +7.05 mV. The zeta potential of +7.05 mV helps to resist the aggregation of colloidal particles, thereby achieving the effect of antibacterial and reducing inflammatory response.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The purpose of the present application is to enhance the biological activity of titanium alloy dental implants by subjecting the titanium alloy dental implants to thermoelectrochemical oxidation treatment. By improving the electrolyte system and adjusting the reaction electrical parameters, a coating which maintains a porous structure and has higher binding strength and a higher phosphorus content is obtained on the surface of the titanium alloy. The zeta potential characteristics of the coating provide the possibility for better antibacterial effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Combined with the following Figure 1 When read together, the above and other features of the present application will be more fully described. It is understood that these drawings only depict several implementations of the present application and should not be considered as limiting the scope of the present application. By using the drawings, the present application will be more clearly and detailed.

[0019] Figure 1 This is the front view of the SEM photograph of the thread plane of the implant sample in the embodiment.

[0020] Figure 2 It is a stereoscopic image of the SEM photograph of the thread side of the implant sample in the embodiment.

[0021] Figure 3 : This is the EDS spectrum of the crater-shaped porous coating containing phosphorus in the example. DETAILED DESCRIPTION

[0022] The following examples are described to assist the understanding of the present application, and the examples are not and should not be interpreted in any way as limiting the scope of protection of the present application.

[0023] The present application relates to a method for improving the bone integration and antibacterial ability of titanium alloy dental implants, and the specific steps are as follows:

[0024] Step 1: preparing an electrolyte, wherein the electrolyte includes: phosphate ions, hydroxide ions, EDTA ions, sodium ions or potassium ions, wherein the phosphate concentration is 5 to 20 mol / L, the hydroxide ion concentration is 5 to 10 mol / L, and the EDTA ion concentration is 1 to 3 mol / L;

[0025] Step 2: Immerse the titanium alloy dental implant substrate in the electrolyte prepared in step 1 for thermo-electrochemical oxidation treatment until a crater-shaped porous coating containing phosphorus is formed. The conditions of the thermo-electrochemical oxidation treatment are: the positive current of the pulse power supply is 8 to 14 A / dm2, the negative current is 6 to 16 A / dm2, the duty cycle is 70% to 100%, and the reaction time is 10 to 20 minutes.

[0026] The coating thickness was measured using an A45CNSS eddy current thickness gauge, and the coating thickness was controlled to be 10-15±1 μm.

[0027] like Figure 1-2 As shown, the microscopic morphology of the crater-shaped porous coating containing phosphorus element was observed under a S-3700N scanning electron microscope (SEM), and the coating had a crater-shaped porous structure.

[0028] The element composition of raw material titanium alloy before measurement using ICP-OES:

[0029] Raw materials Titanium alloy dental implant substrate composition is shown in Table 1 below:

[0030] Table 1

[0031]

[0032] The elemental composition of the crater-shaped porous coating containing phosphorus after treatment was analyzed using the matching Xplore 15 energy dispersive spectrometer (EDS). Figure 3 As shown in Table 2 below,

[0033] Table 2

[0034] Element Wt% At% OK 21.79 43.71 PK 10.68 11.06 TiK 67.53 45.23 Matrix Correction ZAF

[0035] EDS detected that the phosphorus content reached 11.06% by atomic percentage, and the rest were oxygen and titanium.

[0036] To analyze the ability of the coating to inhibit the release of titanium alloy elements, three different polar solvents, namely non-polar (n-calcined), medium polar (isopropanol) and polar (purified water), were used. After 72 hours (maximum time) of extraction, the coated implant samples were subjected to extreme extraction under dynamic shaking (52±2℃, 72±2h), and the obtained extractables were subjected to ICP-MS element impurity detection.

[0037] It was found that the color, clarity and precipitate particles of the n-hexane extract, isopropanol extract and purified water extract had no obvious changes compared with the extraction solvent, which indicated that there were no other harmful components in the crater-shaped porous coating containing phosphorus.

[0038] Chemical characterization and toxicological analysis tests were performed as follows: According to the 20 elements of focus in ICH Q3D (R2) (Cd, Pb, As, Hg, Co, V, Cr, Ni, Li, Sb, Ba, Mo, Cu, Zn, Fe, Mn, W, Se, Sn and Al); according to the 10 elements of focus in the guidelines for pharmaceutical glass (Pb, Co, Cd, As, Li, Sb, Ba, Fe, Zn and Cr); combined with the actual element composition added to the sample and the results of element semi-quantitative analysis experiments, 21 element impurities (Li, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Mo, Cd, Sn, Sb, Ba, W, Hg and Pb) were screened out for ICP-MS quantitative study.

[0039] The 20 elemental impurities that are of particular concern in ICH Q3D(R2) were not detected and exceeded their limits.

[0040] The bonding strength between the crater-shaped porous coating containing phosphorus element and the titanium alloy dental implant substrate was tested by the pulling method.

[0041] Qiao LP reported that the bonding strength between the crater-shaped porous coating containing phosphorus and the titanium alloy dental implant substrate did not exceed 8MPa, while the bonding strength between the crater-shaped porous coating containing phosphorus and the titanium alloy dental implant substrate after being treated by the present application reached 20MPa.

[0042] The Zeta potential of the coating was measured using a SurPASS33 Zeta potential meter. Zeta potential is the potential difference between the continuous phase and the stable layer of fluid attached to the dispersed particles. Zeta potential is a measure of the strength of mutual repulsion or attraction between particles. Since human blood and tissue fluid can be regarded as fluids containing molecules or dispersed particles, bacteria, inflammatory factors, etc. can be regarded as dispersed particles in blood and tissue fluid. Studies have shown that high positive Zeta potential can resist the aggregation of bacteria and inflammatory factors, thereby achieving antibacterial and reducing inflammatory responses.

[0043] When the pH of body fluid is 6.5-7, the zeta potential of the surface of the crater-shaped porous coating containing phosphorus element is detected to be +7.05mV, while the zeta potential of the surface of ordinary TA4 titanium alloy is around 0mV.

[0044] When the zeta potential is 0-5mV, colloids in the solution, such as bacteria and inflammatory factors, will quickly coagulate, leading to inflammation and adverse reactions. Therefore, a zeta potential of +7.05mV helps to resist the coagulation of colloidal particles, thereby achieving antibacterial and inflammatory effects.

[0045] The purpose of the present application is to enhance the biological activity of titanium alloy dental implants by subjecting the titanium alloy dental implants to thermoelectrochemical oxidation treatment. By improving the electrolyte system and adjusting the reaction electrical parameters, a coating which maintains a porous structure and has higher binding strength and a higher phosphorus content is obtained on the surface of the titanium alloy. The zeta potential characteristics of the coating provide the possibility for better antibacterial effects.

[0046] Although the present application has disclosed multiple aspects and embodiments, other aspects and embodiments will be obvious to those skilled in the art, and several modifications and improvements may be made without departing from the concept of the present application, all of which belong to the protection scope of the present application. The multiple aspects and embodiments disclosed in the present application are only for illustration and are not intended to limit the present application. The actual protection scope of the present application shall be subject to the claims.

Claims

1. A method for improving the bone integration and antibacterial ability of titanium alloy dental implants, characterized by: The specific steps are as follows: Step 1: preparing an electrolyte, the electrolyte comprising: phosphate ions, hydroxide ions and EDTA ions, wherein the phosphate concentration is 5 to 20 mol / L, the hydroxide ion concentration is 5 to 10 mol / L, and the EDTA ion concentration is 1 to 3 mol / L; Step 2: Immerse the titanium alloy dental implant substrate in the electrolyte prepared in step 1 for thermo-electrochemical oxidation treatment until a crater-shaped porous coating containing phosphorus is formed. The conditions of the thermo-electrochemical oxidation treatment are: The positive current of the pulse power supply is 8-14A / dm2, the negative current is 6-16A / dm2, the duty cycle is 70%-100%, and the response time is 10-20 minutes; The phosphorus content of the crater-shaped porous coating containing phosphorus after the treatment in step 2 is 11.06% by atomic percentage; The coating bonding strength between the crater-shaped porous coating containing phosphorus element and the titanium alloy substrate after the treatment in step 2 reaches 20MPa; The zeta potential of the surface of the crater-shaped porous coating containing phosphorus element after treatment in step 2 is +7.05 mV. The zeta potential of +7.05 mV helps to resist the aggregation of colloidal particles, thereby achieving the effect of antibacterial and reducing inflammatory response.

2. A method for improving the bone integration and antibacterial ability of titanium alloy dental implants according to claim 1, characterized in that: The electrolyte also includes sodium ions or potassium ions.

3. The method for improving the bone integration and antibacterial ability of titanium alloy dental implants according to claim 1, characterized in that: The thickness of the crater-shaped porous coating containing phosphorus element is controlled to be 10 to 15±1 micrometers.

4. The method for improving the bone integration and antibacterial ability of titanium alloy dental implants according to claim 1, characterized in that: The components of the crater-shaped porous coating containing phosphorus after the treatment in step 2 are phosphorus, oxygen and titanium.

Citation Information

Patent Citations

  • Metal implants with antibacterial and bone integration promoting functions and their preparation methods

    CN107648674B

  • A nitrogen-doped titanium oxide coating, its preparation method and application

    CN110180020B

  • Rotatable medical and / or dental instrument having a variable speed transmission

    WO2000012021A1

  • Arrangement with an implant and / or a unit belonging to said implant, and method for production of the implant and / or unit

    WO2005055860A1

  • Nitrogen-doped titanium oxide coating and preparation method and application thereof

    CN110180020A